Brand Image, Lifestyle, and Advertising on Purchase Decisions of Make Over Products at Chan Collection Store in Denpasar - Anthonio, Febrian Sila; Pulawan, Made; Dewi, I Gusti Ayu Agung Istri Sari (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2024)
This study aims to examine and analyze the influence of brand image, lifestyle, and advertising on the purchase decisions of Make Over products. Using a sample of 100 respondents selected with the Slovin formula, data were analyzed through multiple linear regression and hypothesis testing. The findings reveal that brand image, lifestyle, and advertising significantly impact purchase decisions. A positive relationship exists between brand image and purchase decisions, indicating that a stronger brand image leads to higher purchase decisions. Similarly, lifestyle positively affects purchase decisions, suggesting that a higher lifestyle corresponds to increased purchase decisions. Additionally, advertising has a positive influence, implying that more advertising leads to higher purchase decisions.